1999
DOI: 10.2527/1999.7761422x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term administration of recombinant bovine somatotropin (Posilac) and Synovex on performance, plasma hormone and amino acid concentration, and muscle and subcutaneous fat fatty acid composition in Holstein-Friesian bull calves.

Abstract: The effect of recombinant somatotropin (rbST), Synovex (Syn), and their combination (rbST+Syn) on intact male calves was examined in an experiment that lasted an average of 238 d. Holstein-Friesian bull calves were allotted to one of four subtreatments (n = 14/treatment) in a factorial arrangement. There were two levels of rbST (0; rbST) and two levels of the estrogenic growth promoter Synovex (0; Syn). The rbST was administered once every 2 wk as injections of 500 mg of Posilac. Synovex (C and S) was implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
3
9
1
3
Order By: Relevance
“…Early et al (1990), avaliando o efeito da aplicação de rBST em 20 novilhos, por um longo período (112 dias), não observaram diferença significativa para a IMS entre os animais controle (7,9 kg) e os que receberam 20,6 mg/dia de rBST (8,1 kg). Da mesma forma, Holzer et al (1999), trabalhando com machos inteiros e doses de 500 mg de rBST (Posilac®) a cada 14 dias durante 236 dias de experimento, não observaram influência sobre a IMS (8,7 kg para os animais tratados e 8,8 kg para os animais controle). No entanto, Rumsey et al (1996) observaram aumento de 2,3% na IMS para novilhos tratados com rBST em comparação com tratamento controle.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Early et al (1990), avaliando o efeito da aplicação de rBST em 20 novilhos, por um longo período (112 dias), não observaram diferença significativa para a IMS entre os animais controle (7,9 kg) e os que receberam 20,6 mg/dia de rBST (8,1 kg). Da mesma forma, Holzer et al (1999), trabalhando com machos inteiros e doses de 500 mg de rBST (Posilac®) a cada 14 dias durante 236 dias de experimento, não observaram influência sobre a IMS (8,7 kg para os animais tratados e 8,8 kg para os animais controle). No entanto, Rumsey et al (1996) observaram aumento de 2,3% na IMS para novilhos tratados com rBST em comparação com tratamento controle.…”
Section: Resultsunclassified
“…Entretanto, Vann et al (1998), avaliando a administração de rBST no aumento da massa muscular em bezerros em creep-feeding, observaram que os tratamentos com rBST não diferiram do controle para RC e para peso dos órgãos internos. Resultados semelhantes foram obtidos por Holzer et al (2000), trabalhando com bezerros Holstein-Friesian, administrando 500 mg de rBST (Posilac®) a cada 14 dias, durante 240 dias de experimento.…”
Section: Parameters Treatmentsunclassified
“…In contrast, other studies with estrogen-implanted bull calves [12] or steers [13] found reduced SFA and increased MUFA. In the same studies, Hozler et al [12] and Ibrahim et al [13] reported a decrease and an increase in the proportions of polyunsaturated FA (PUFA), respectively. In general, the available information on the effects of growth promoting implants on beef FA composition are inconclusive.…”
Section: Introductionmentioning
confidence: 70%
“…Regarding FA composition, studies with estrogen- or androgen-implanted steers showed small increases in the proportions of saturated FA (SFA) and decreases in proportions of monounsaturated FA (MUFA) [10,11]. In contrast, other studies with estrogen-implanted bull calves [12] or steers [13] found reduced SFA and increased MUFA. In the same studies, Hozler et al [12] and Ibrahim et al [13] reported a decrease and an increase in the proportions of polyunsaturated FA (PUFA), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 Os níveis plasmáticos de colesterol total não foram influenciados pela aplicação de r-bST em dose única ou a cada 14 dias, em novilhas meio-sangue Nelore x Red Angus (Prado et al, 2003). Holzer et al (1999), avaliando os efeitos da r-bST e progesterona + benzoato de estradiol, ao longo de 240 dias de experimento, em animais da raça Holandesa, não observaram diferença entre os tratamentos para as concentrações do colesterol total. Da mesma forma, Holzer et al (2000), trabalhando com dois níveis de energia na dieta e dois níveis de r-bST, administrados em intervalos de duas semanas, também não observaram diferença entre os tratamentos em relação às concentrações desse metabólito.…”
Section: Resultsunclassified